I used quotient rule and chain rule. The solution keep getting is wrong. I think my algebra is off.:
Follow Math Help Forum on Facebook and Google+
y'=3{(x^2+1)/(x^2-1)}^2 * {2x(x^2-1)-2x(x^2+1)}/{x^2-1}^2=... } =3{(x^2+1)/(x^2-1)}^2 * {2x{x^2-1-x^2-1}/{(x^2-1)^2}= =3{(x^2+1)/(x^2-1)}^2 * {2x{-2}/{(x^2-1)^2}= =3{(x^2+1)/(x^2-1)}^2 * {-4x/{(x^2-1)^2}= =-12x/(x^2-1)}^4
Originally Posted by superduper1 I used quotient rule and chain rule. The solution keep getting is wrong. I think my algebra is off.: show your work so that someone may see your mistake.
I get take out common factors to do some additional cancellations.
I think the mistake is somewhere after here: What is this when simplified? I think this is throwing me off. The 3 in front and the ^2 in the back